Cytotoxic chemotherapy may overcome the development of acquired resistance to epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) therapy. Issue 3 (September 2015) - Kanda, Shintaro; Horinouchi, Hidehito; Fujiwara, Yutaka; Nokihara, Hiroshi; Yamamoto, Noboru; Sekine, Ikuo; Kunitoh, Hideo; Kubota, Kaoru; Tamura, Tomohide; Ohe, Yuichiro
Highlights A phase II trial of gefitinib with inserted cisplatin plus docetaxel therapy. Patients with advanced non-small cell lung cancer harboring EGFR mutations were enrolled. The median progression free survival (PFS) was 19.5 months and 5-year PFS rate was 22.0%. The median survival time was 48.0 months and 5-year survival rate was 36.5%. The insertion of chemotherapy might prevent the acquired resistance to EGFR-TKIs.